VARIABLE ORDER FRACTIONAL DISCRET SYSTEMS AND APPLICATIONS - BOUKHOBZA, Meriem (l’Université de Mostaganem, 2025)
The aim of this work is to develop recent methods for the stability of variable order fractional system in discret -time .In particular, during the project of this doctorate thesis we present the theory of variable order fractional calculus and discret-time calculus to prove the questions of existence and uniqueness results, stability and others properties with applications to different biological systems
Keywords: Variable-order fractional derivative;fractional discrete calculus; Optimal control; stability; fixed point techniques;numerical simulation